Sociedade de risco e meio ambiente: o papel do estado na gestão compartilhada do patrimônio cultural - Zani Cajueiro Tobias de Souza (2013)
Cultural heritage has been considered mostly as an element of the environment. Thus, not only for its importance, that became from its values, but also because of growing concern about environmental bias, thanks to globalization and the growing risk, there is need for all stakeholders engaged in preserving their roles. If popular participation is essential, it remains impossible not to recognize that the role of the state is still prevalent, even when comparing cultures and different stages of development and environmental protection is still seen as an obstacle to economic growth. The mitigation required and mandatory state intervention, according to the three functions of power can be extremely harmful. The purpose of this study is to analyze how it operated in the national and international legal framework, one insertion, as well as their consequences. Also, if the law supports national environmental policy and the principle of state intervention required to outline the current state of protection and enforcement of environmental principled basis. The work was developed based on literature review and case studies, with no pretension, obviously, of exhausting the topic of discussion but to reflect about the implementation of protection in its fullest extent, to benefit and meet the present and future generations.